Effects of crystalline menthol on blood metabolites in Holstein steers and in vitro volatile fatty acid and gas production - Van Bibber-Krueger, C. L.; Miller, K. A.; Aperce, C. C.; Alvarado-Gilis, C. A.; Higgins, J. J.; Drouillard, James S. (My University, 2016)
Fifty-two Holstein steers (573 +/- 9.92 kg BW) were used to determine if oral administration of crystalline menthol would induce changes in endogenous secretions of IGF-1 and circulating concentrations of glucose, lactate, and plasma urea nitrogen (PUN). Steers were blocked by BW and assigned within block to treatment. Treatments consisted of 0, 0.003, 0.03, or 0.3% crystalline menthol (DM basis) added to the diet. Animals were housed in individual, partially covered pens equipped with feed bunks and automatic water fountains. On d 1 of the experiment, blood samples were obtained via jugular venipuncture at 0, 6, 12, 18, and 24 h after feeding. Treatment administration commenced on d 2, and blood samples were again drawn at 0, 6, 12, 18, and 24 h after feeding. This blood-sampling schedule was repeated on d 9, 16, 23, and 30. Plasma was analyzed for PUN, glucose, and lactate concentrations. Serum was used to analyze IGF-1 concentration. Body weights were measured on d 1, 9, 16, 23, and 30. To accompany the live animal phase, in vitro fermentations were performed using ruminal fluid cultures. Measurements included VFA concentrations and fermentative gas production for cultures containing crystalline menthol at 0, 0.003, 0.03, or 0.3% of substrate DM. Addition of menthol to the diet of steers resulted in a treatment x day interaction (P < 0.01) for concentrations of IGF-1, PUN, and plasma glucose. Cattle fed 0 and 0.003% menthol had greater serum IGF-1 concentrations on d 2 compared with steers fed 0.03% menthol. Steers fed 0% menthol had greater serum IGF-1 concentrations on d 9 compared with steers fed 0.03 and 0.3% menthol, whereas no differences were observed on d 23 or 30. Plasma glucose was similar among treatments until d 23, when steers supplemented with 0.03% menthol had lower glucose concentrations. Plasma urea nitrogen concentrations were not different among treatments; however, PUN concentrations varied by day. A linear response was detected for BW (P = 0.03), with steers consuming 0% menthol having the greatest BW and steers that consumed 0.3% menthol having the lightest BW until d 30. A menthol x day interaction was observed for daily feed deliveries (P < 0.01): cattle fed 0.3% menthol consumed less feed from d 5 through 12. Furthermore, in vitro gas production and VFA concentrations were unaffected by addition of menthol (P > 0.21). In conclusion, menthol supplementation minimally affected blood parameters associated with growth or ruminal fermentative activity.
Citation: Van Bibber-Krueger, C. L., Miller, K. A., Aperce, C. C., Alvarado-Gilis, C. A., Higgins, J. J., & Drouillard, J. S. (2016). Effects of crystalline menthol on blood metabolites in Holstein steers and in vitro volatile fatty acid and gas production. Journal of Animal Science, 94(3), 1170-1178. doi:10.2527/jas2015-8779
Keywords: Insulin-Like Glucose Factor 1; Menthol; Plasma Urea Nitrogen; Ruminant; Essential Oils; Piperita L.